What Do We Know About Investment of Zakat Fund? A Systematic Literature Review - Ainun Ruzana (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Various works of literature have been written about zakat, as one of the most powerful Islamic Economics instruments, in the light of sustainable development. From an economic point of view, investment denotes activities involving capital expenditure that give up current expenditure for possible returns in the future. Investment in zakat fund is done with the purpose to increase the future probable income of the asnaf, contrary to the consumptive way of zakat distribution. There are lots of discourses that criticized the consumptive and conventional modes of distribution of zakat. However, studies on the potential of income generation from the investment of zakat funds, to ensure the sustainability and productivity of zakat distribution are still very limited. Hence, this study aims to systematically review the academic discourse around the investment of zakat funds, to identify the themes and sub-categories of previous studies. This is done to identify the research gaps that exist and to suggest the areas that are of much potential to be explored with regards to investment of zakat fund but require further study.